Hubungan Perilaku Merokok Terhadap Keberhasilan Pengobatan Pada Pasien Tuberkulosis Di Puskesmas Kecamatan Johar Baru Jakarta Pusat, Tahun 2016 - J, Winda Afdilla (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2018)
Tuberculosis (TB) is an infectious disease that poses one of the major threats to humans. To deal with all threats from tuberculosis, WHO has developed a TB control strategy known as the DOTS strategy to improve the success of TB treatment with the indicator used being cured and complete treatment. The success of treatment is influenced by internal and external factors such as smoking. This study aims to determine the relationship of smoking behavior with the success of tuberculosis treatment at community health center of JoharBaru Central Jakarta in 2016. This research was conducted by Cross-Sectional non-experimental quantitative method. Population and sample are adult tuberculosis patients registered at community health center of JoharBaru Central Jakarta in 2016. Samples are selected by using Simple Random Sampling. The data were collected by interview using questionnaire. Data analysis using SPSS with Chi-Square test. Result: There were 45 respondents (80,4%) succeed in tuberculosis treatment with 25 people (83,9%) of respondents who did not smoke. Results of statistical tests using Chi-Square test obtained value P = 0.69 (>0,05). There is no relation between smoking behavior with the success of tuberculosis treatment at community health center of JoharBaru Central Jakarta in 2016. Keywords:Smoking Behavior, Success of Tuberculosis Treatment